Iron-porphyrin encapsulated in poly(methacrylic acid) and mesoporous Al-MCM-41 as catalysts in the oxidation of benzene to phenol - Nur, Hadi; Hamid, Helda; Endud, Salasiah; Hamdan, Halimaton; Ramli, Zainab (Elsevier, 2006)
Poly(methacrylic acid) (PMAA) and mesoporous molecular sieve Al-MCM-41 with Si/Al = 20 were used as supports for the encapsulation of bulky iron(III)-5,10,15,20-tetra-(4-pyridyl)porphyrin (Fe-TPyP). Metalloporphyrin of Fe(III) was encapsulated inside the mesopores of Al-MCM-41 by a process of sequential synthesis of Fe-TPyP by treatment of FeCl3 with 5,10,15,20-tetra-(4-pyridyl) porphyrin (TPyP), followed by encapsulation of Fe-TPyP. Fe-TPyP complexes were also successfully encapsulated in PMAA by polymerizing a monomer (MAA) with a cross-linker around the Fe-TPyP complexes. The materials obtained were identified using XRD, UV-vis DR, FTIR and luminescence spectroscopies. The oxidation of benzene to phenol using aqueous hydrogen peroxide has been studied using both iron-porphyrin encapsulated in poly(methacrylic acid) and mesoporous Al-MCM-41 as catalysts. The encapsulated iron-porphyrin in PMAA (Fe-TPyP-PMAA) give a higher catalytic activity compared to Fe-TPyP encapsulated in Al-MCM-41 (Fe-TPyP-MCM-41). However, the product selectivity and the regenerability of Fe-TPyP-PMAA are not as good as than those of Fe-TPyP-MCM-41. One considers that the hydrophobic nature of Fe-TPyP-PMAA may account for the high catalytic activity, and the ordered structure of Fe-TPyP-MCM-41 may contribute to a high selectivity.